The Analysis and Comparison of Models of Demand for Goods in Marketing - Pocevičius, Darius (Ekonomika, 1997)
Marketing theory and marketing management require information about consumer demand. Several economic and marketing approaches of modeling consumer demand are reviewed (consumer budget allocation with seperable preferences, Lancaster's approach, the joint space model and the defender model). Their strengths and weaknesses are evaluated with respect to marketing needs.